The Predictive Ability of Social Support at the Level of Psychological Immunity among Refugee Women in the Palestinian Refugee Camps - Alsadi, Rihab (Al-Adab Journal, 2024)
The current study aimed to know the level of social support and psychological immunity among a sample of refugee women in the Palestinian refugee camps. The study also aimed to uncover the statistically significant differences in the level of social support and psychological immunity according to the two variables of age and the educational level, and to ascertain also the predictive ability of social support in the psychological immunity. The sample of the study consisted of 228 refugee women in Jenin refugee camp who were chosen by the random sample method. The results of the study showed that the level of social support and psychological immunity was high. The study concluded that there are no statistically significant differences at the significance level of (0.05≤ a) in the level of social support and psychological immunity among the refugee women which are ascribed to the variable of age. However the results indicated that there are no statistically significant differences at the significance level of (0.05≤ a) in the psychological immunity among the refugee women which are ascribed to the variable of (educational level). However there are differences in the level of social support which are ascribed to the variable of educational level in favour of the master’s degree and higher. The study also concluded that the social support has a predictive ability which is statistically significant in the level of psychological immunity among the refugee women.